EFFECT OF BIOACTIVE PROTEIN INGREDIENTS (MOTIVTM) ON TOTAL HEMOCYTE AND SURVIVAL RATE OF VANNAMEI SHRIMP, Litopenaeus vannamei - Slamet Budi Prayitno; Bagus Rimbayu Ardie; Romi Novriadi; Vivi Endar Herawati; Seto Windarto (Indonesian Aquaculture Journal, 2022)
One of the problematic factors in the cultivation of vannamei shrimp is the outbreak of bacteria and viruses. One way to prevent infection is by strengthening the shrimp’s immune system. MOTIVTM is a fermented corn protein concentrate that has been reported to possess probiotic properties that can positively increase the disease resistance of shrimp. Therefore, this study aimed to determine the effect of bioactive protein (MOTIVTM) on the total hemocyte count and shrimp survival rate. The study used an experimental method with a completely randomized design with five treatments and three replications: A (commercial feed), B (7.5% MOTIV add of 1.5% krill meal instead of 9% fish meal), C (7.5% MOTIVTM add of 1% krill meal to replaces of 2% poultry meal and 6.5% fish meal), D (7.5% MOTIVTM to replaces of 3.5% poultry meal and 4% fish meal), and E (7.5% MOTIVTM to replaces of 7.5% poultry flour). Feeding was done four times/day based on shrimp biomass and weekly feed counts based on daily shrimp survival. The vannamei shrimp used was one gram with a population density of 15 shrimps/aquarium with an aquarium volume of 100 liters.Total shrimp hemocytes, survival, and water quality were all measured. Treatment C had the highest total hemocyte, averaging 4.1 x 107 cells/mL, whereas treatment B had the lowest, averaging 1.4 x 107 cells/mL. During the trial, only treatment C supported 100% survival.